SISTEM E-CRM PADA KLINIK TUMBUH KEMBANG ANAK INDIGROW - Ongowarsito, Henkie; Gitarani, Hesty (CommIT (Communication and Information Technology) Journal, 2008)
Parents of children with special needs generally face skepticism from within himself and rejection from family or the environment when faced with the fact that their children are special children. Therefore, they need environments where they can share with each other so they are more powerful in supporting children to develop. Clinic Indigrow as parents and school partners in developing the child optimally, having a few problems relating to the operation of their services, the problems are: The schedule consultation/evaluation by a doctor that often can not be implemented because the doctor had to attend seminars abroad, oversee the implementation of home programs, and also in providing education and support for parents. With eCRM organization will be able to improve its services to support parents. ECRM for Clinical Development Indigrow starting from the analysis of internal factors and external, and then further analyzed using the SWOT Matrix and Matrix IE to get an alternative strategy in accordance with business conditions Indigrow Clinic. ECRM systems analysis and design were calculated using Object Oriented Analysis and Design (OOA & D) and documented with notations Unified Modeling Language (UML). In accordance with the problems encountered in the initial research, analysis and design, the focus is limited to the field of service. Results of the design is the eCRM system that can be developed and utilized by the Clinic Indigrow to provide more support to parents of patients.Keywords: service, eCRM, indigrow children